(untitled) - Fukumi, Shimura (Tokyo, 2019)
The Music of Color collects some of Shimura's most insightful writing together with Takao Inoue's stunning photographs of her art and the natural world that inspires it. From winter snows to spring blossoms, from the foothills of Japan's “Southern Alps" to the back streets of Gion, Kyoto, Shimura initiates the reader into a facet of Japanese culture where the boundary between craft and art is blurred. Her insight into the sources and uses of natural color, along with her decades of experience in the world of Japanese textiles, from silkworm and loom to finished kimono, are both on full display in this rich collection
Keywords: Nhà thiết kế dệt may,Textile designers; Nhật Bản,Japan